Application of Taguchi and Box-Behnken designs for surface roughness in precision grinding of silicon. (19th January 2011) - Alao, A-R.; Konneh, M.
This study reports the use of Taguchi and Box-Behnken designs for minimising surface roughness in precision grinding of silicon using resin-bonded diamond mounted wheels. Taguchi method was used to study the effect and optimisation of grinding parameters while Box-Behnken method was utilised to develop a mathematical model relating the average surface roughness to the grinding parameters, depth of cut, feed rate and spindle speed. An orthogonal array (OA), the signal-to-noise (S/N) ratio, and the analysis of variance were employed to find the minimal surface roughness. Confirmation tests were carried out in order to illustrate the effectiveness of the Taguchi method. The results show that feed rate mostly affected the surface roughness. The predicted surface roughness (Ra ) of 34 nm was in agreement with the confirmation tests. Massive ductile-streaked surface was also found corresponding to the minimal surface finish determined from the optimal levels. A second-order model has also been established between the grinding variables and the surface roughness. The model is adequate to navigate the design space.